REMEMBERING XIAO SHAN IN BA JIN ESSAYS THE WOUNDS OF THE CULTURAL REVOLUTION - Alkaff, Nadira; Gunawan, Hin Goan (Bambuti, 2020)
The Cultural Revolution era was a dark period in Chinese history. The resistance to the power of Chairman Mao by literati people has resulted in deep wounds, as a result of intimidation, bad stigma, exclusion, and even imprisonment which often ends in death. Ba Jin's essay Remembering Xiao Shan can be seen as a mirror reflecting the deep wounds experienced by the author who is accused of being part of a counterrevolutionary group. Not only himself, but his beloved wife also had to bear the wounds of the Cultural Revolution. This study uses a hermeneutical analysis model to explore the author's "living world" in the text Reminiscing Xiao Shan about the sorrow experienced by himself, his fellow authors who were labeled as part of right-wing resistance, and the people he loved during repressive times under the control of Mao Zedong. The Cultural Revolution was long gone, but the wounds it caused were not easy to heal, and so Ba Jin documented it in the text in the form of an essay. In the end, time has proved that the idea of ​​resistance carried out by people like Ba Jin is irresistible, as has been proven by the current capitalistic economic style in China. The close people, even Ba Jin's wife were indeed neglected by the Red Guards, but their thoughts are still alive today.